An Experimental Study of Capillary Tubes Behavior With R-12 and R-134a - Ali, Issam M.; .Jasim, Hani A (Al-Khwarizmi Engineering Journal, 2017)
Experimental work has been performed on three capillary tubes of different lengths and diameters using R-12 and R-134a. The test also studies the effect of discharge and speed of evaporator fan. The results clearly showed that refrigerant type and discharge significantly influence the temperature drop across the capillary tube. While the speed of evaporator fan has small effect. Experimental results showed that the temperature gradient for the two refrigerants are the same, but after approximatly one meter the temperature gradient of R-134a  is steeper than R-12.